Some special physical abilities and their relationship to the skill of remote shooting with hand reel - Sabeeh Obaid, Nahlah (International Journal of Psychosocial Rehabilitation, 2020)
Sports excellence indicates the intellectual and scientific advancement of society because it is the result of training based on science and experience for individuals who have physical fitness and physical characteristics and are distinguished from others by many of the qualities that lead them to the highest levels of optimal achievement, and handball is one of the sports that are widely practiced It occupies a good position as it is an interesting game, and the physical preparation with its various elements is the most important component of mathematical preparation in all games, including the game of handball and what it needs in implementing its skills to some special structural abilities, and because the handball game includes offensive and defensive skills, which varies in its needs to the types of abilities The special physical and appropriate skills of these skills, and among these skills is the correction skill, which has a decisive role in handball matches. The importance of the research lies in the fact that it is an attempt to identify the relationship between some of the physical abilities of the remote aiming skill of handball among the players of the National Center for Sports Talent Care of the 2Ministry of Youth and Sports of Iraq for handball at ages (16-17) years of handball in Iraq, with the exception of the Kurdistan Region for the 2018 sports season 2019, which is a reliable indicator in the process of training and selecting players in the handball game.